(3KdGKjGJ GdCaYGd Gdebhd ajgG nCanYd ChoCapYd HeYfi hGMO hRhGFOgs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3jMi GdOjSWi Hf aNQ GdOjf Hf Ydi Hf TeS GdOjf eMeO GdeGdci s)
(3ChdgG (B:s
(3bGd TjNfG gPG cJGH CPcQ ajg eG JjSQ ef KdGKjGJ GdCaYGd Gdebhd ajgG CaYd hCaYd HeYfi hGMO , eQJHkG Ydi MQha GdeYLe aCHOC HeG Chdg geRI s
(3BNQgG (B:s
(3heG Hfi QHGYjI ddeaYhd OGFekG hKdGKjI ddaGYd (B: (3CfcQ fcQkG hfcGQI hCfcQ hfcQ hefcQ Ci OGgHI , hOGf OhfkG hCOjf VYa , s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3eQJH Ydi MQha GdeYLes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs